Humoral immune response to hypervariable region 1 of the putative envelope glycoprotein (gp70) of hepatitis C virus. - Kato, N (1993)
We recently found that alterations of amino acids in hypervariable region 1 (HVR1) of the putative envelope glycoprotein (gp70) of hepatitis C virus (HCV) occurred sequentially in the chronic phase of hepatitis at intervals of several months. This finding suggests that mutations in HVR1 are involved in the mechanism of persistent chronic HCV infection involving escape from the immunosurveillance system. To explore this possibility, we examined the humoral immune response to HVR1 with our assay system, in which immunoprecipitation was carried out with sera from patients by using an HVR1 (27-amino-acid) dihydrofolate reductase fusion protein synthesized by in vitro transcription and translation. Results showed that HVR1 contains a sequence-specific immunological epitope that induces the production of antibodies restricted to the specific viral isolate. Furthermore, analysis of the kinetics of the appearance of antibodies in two patients with chronic hepatitis, with whom successive alterations of amino acids of HVR1 have been observed, showed that the titers of anti-HVR1 antibodies usually reached maximal levels several months after the isolation of HCV having the specific sequence of HVR1. This observation suggests that anti-HVR1 antibodies are involved in the genetic drift of HVR1 (minor antigenic variation) by immunoselection. However, the coexistence of HVR1 as an antigen and its specific antibody was sometimes observed. The possibility that HVR1 acts as a neutralizing epitope is discussed.